Emotional Intelligence and Stress Coping Strategies Among Students of Physical Education and Sport Study Programs - Romualdas Malinauskas; Tomas Saulius; Giedrius Kaufmanas (Lithuanian Sports University, 2020)
Background. Studies of various scholars confirm the relation between the application of stress coping strategies and emotional intelligence, but there is a lack of research about the relationship between individual coping strategies and emotional intelligence levels among the first- and the fourth-year students. The aim of the research was to reveal peculiarities of emotional intelligence and stress coping strategies of undergraduate students of physical education and sport study programs. Methods. The Shutte Self-Assessment Questionnaire was used to measure the level of emotional intelligence of the participants (Schutte & Malouff, 1999). The questionnaire composed by Grakauskas and Valickas (2006) was used to identify the stress coping strategies. It consists of four factors: social support factor, problem-solving factor, emotional discharge factor and avoidance factor. The research was based on the following ethical principles: confidentiality, anonymity, impartiality and privacy. The first- and the fourth-year students of the Lithuanian Sports University and Lithuanian University of Educational Sciences, Physical Education and Sports Programs were surveyed. The research sample consisted of 123 participants. Male participants comprised 66.7% of the sample, and the female participants comprised 33.3%. of the sample. The first-year undergraduates made up 57.7% of the sample, and the fourth-year undergraduates made up 42.3% of the sample. Results. Analyzing the data on the stress coping strategies according to the participants studying experience, it was found that the fourth-year students used the social support strategy more frequently in comparison with the first-year students. In addition, the fourth-year students applied emotional discharge and avoidance strategies more often than the first-year students. Comparing stress coping strategies and emotional intelligence according to the gender of participants, no statistically significant differences were found. There was a statistically significant relationship between the stress coping strategy and the ability to evaluate and express one's emotions. Conclusions. Comparing emotional intelligence of the first- and the fourth-year students of physical education and sports study programs, no statistically significant differences were found. Comparison of stress coping strategies applied by the first- and the fourth-year students of physical education and sports degree programs revealed that the fourth-year students tended to use social support, emotional discharge and avoidance strategies more frequently than the first-year students. Comparison of stress coping strategies and emotional intelligence according to gender did not show any statistically significant differences. However, there was a statistically significant relationship between stress coping strategies and emotional intelligence, though it was a weak, but significant difference between emotional intelligence components such as the ability to express and manage emotions and problem-solving focused stress coping strategy. Keywords: stress, stress management strategies, emotional intelligence.